HTLV-1 Is Also a Sexually Transmitted Infection - Martel, Mariana; Gotuzzo, Eduardo (Frontiers in Public Health, 2022)
HTLV-1 is a retrovirus which causes diverse diseases in 10% of its infected population, significantly worsening their quality of life and mortality rate. Even though it is globally distributed and is endemic in many countries (including Peru), it is still highly neglected. It spreads through vertical, sexual and parenteral transmission. As no effective treatment against this virus exist, prevention is required to contain it. The World Health Organization published a technical report on the matter in 2021, with the collaboration of international HTLV-1 experts. However, neither the impact of sexual transmission (cause of the majority of adult cases and infection in non-endemic areas) nor its prevention were considered. Evidence is presented, which shows the magnitude of sexual transmission, its risk factors and preventive measures; hoping it will encourage health workers to help eradicate this infection.